Factors Affecting Knowledge About The Danger Signs Of Pregnancy (INCH : Journal of Infant and Child Healthcare, 2023)
Pregnancy is a state of containing a developing embryo or fetus in a woman's body. Most women feel aches and pains during their pregnancy. Pregnant women must know the danger signs in pregnancy. Analytical research design with cross sectional / cross-sectional method. This research was carried out at the Tanjung Pura Hospital, Langkat Regency, North Sumatra. Bivariate analysis used Chi Square. The results of the analysis of the relationship between the age of pregnant women with a p value = 0.004 (P < 0.05), the distance between pregnancies with a p value = 0.548 (P > 0.05. gravida with a level of knowledge about danger signs of pregnancy with a p value = 0.027 (P < 0.05) Conclusion There is a relationship between the age of pregnant women and gravida with the level of knowledge about danger signs of pregnancy, there is no relationship between the distance of pregnancy and the level of knowledge about danger signs of pregnancy.